2021
DOI: 10.3389/fneur.2021.683532
|View full text |Cite
|
Sign up to set email alerts
|

Microstimulation Is a Promising Approach in Achieving Better Lead Placement in Subthalamic Nucleus Deep Brain Stimulation Surgery

Abstract: Background: The successful application of subthalamic nucleus (STN) deep brain stimulation (DBS) surgery relies mostly on optimal lead placement, whereas the major challenge is how to precisely localize STN. Microstimulation, which can induce differentiating inhibitory responses between STN and substantia nigra pars reticulata (SNr) near the ventral border of STN, has indicated a great potential of breaking through this barrier.Objective: This study aims to investigate the feasibility of localizing the boundar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In addition to the potential mechanistic insights gained by ascertaining the physiological differences in the synaptic dynamics of inhibitory transmission in STN (persistent) versus SNr (depressed) during HFS, these dynamics can be used as neural biomarkers to delineate these structures from one another during DBS implantation procedures. To this end, previous works have suggested that the duration of neuronal inhibition which persists beyond the cessation of a short-duration microstimulation train of HFS could also be used for such purposes [9,33].…”
Section: Towards Synaptic Dynamics Informed Deep Brain Stimulationmentioning
confidence: 99%
“…In addition to the potential mechanistic insights gained by ascertaining the physiological differences in the synaptic dynamics of inhibitory transmission in STN (persistent) versus SNr (depressed) during HFS, these dynamics can be used as neural biomarkers to delineate these structures from one another during DBS implantation procedures. To this end, previous works have suggested that the duration of neuronal inhibition which persists beyond the cessation of a short-duration microstimulation train of HFS could also be used for such purposes [9,33].…”
Section: Towards Synaptic Dynamics Informed Deep Brain Stimulationmentioning
confidence: 99%